What is systems biology? - Breitling, Rainer (Frontiers in Physiology, 2010)
Systems biology is increasingly popular, but to many biologists it remains unclear what this new discipline actually encompasses. This brief personal perspective starts by outlining the aesthetic qualities that motivate systems biologists, discusses which activities do not belong to the core of systems biology, and finally explores the crucial link with synthetic biology. It concludes by attempting to define systems biology as the research endeavour that aims at providing the scientific foundation for successful synthetic biology.